Response of the periodontal tissues to β-adrenergic stimulation - Moraes, Renata Mendonça [UNESP]; Anbinder, Ana Lia [UNESP]; Elefteriou, Florent (elsevier, 2021)
Aims: Stimulation of β-adrenergic receptors (βAR) in osteoblasts by isoproterenol (ISO) was shown to induce Vascular Endothelial Growth Factor (VEGF) and angiogenesis in long bones. We thus aimed to determine the vascular response of mandibular tissues to βAR stimulation regarding blood vessel formation. Main methods: Six-week-old wild-type C57BL6 female mice received daily intraperitoneal injections of ISO or phosphate buffered saline (PBS) for 1 month. Hemimandibles and tibias were collected for immunolocalization of endomucin, tyrosine hydroxylase (TH), neuropeptide Y (NPY) and norepinephrine transporter (NET). Moreover, Vegfa, Il-1 β, Il-6, Adrb2 and Rankl mRNA expression was assessed in mandibles and tibias 2 h after PBS or ISO treatment. Key findings: Despite similar sympathetic innervation and Adrb2 expression between mandibular tissues and tibias, with TH and NPY+ nerve fibers distributed around blood vessels, ISO treatment did not increase endomucin+ vessel area or the total number of endomucin+ vessels in any of the regions investigated (alveolar bone, periodontal ligament, and dental pulp). Consistent with these results, the expression of Vegfα, Il-6, Il-1β, and Rankl in the mandibular molar region did not change following ISO administration. We detected high expression of NET by immunofluorescence in mandible alveolar osteoblasts, osteocytes, and periodontal ligament fibroblasts, in addition to significantly higher Net expression by qPCR compared to the tibia from the same animals. Significance: These findings indicate a differential response to βAR agonists between mandibular and tibial tissues, since the angiogenic potential of sympathetic outflow observed in long bones is absent in periodontal tissues.
Keywords: Blood vessels; Bone; Periodontitis; Sympathetic nervous system